Tissue preserving non-invasive physical plasma treatment for cervical squamous intraepithelial neoplasia grade 3—a prospective randomized, controlled clinical trial - Henes, Melanie; Matovina, Sabine; Rottscholl, Robert; Feng, You-Shan; Fleischhacker, Antonia; Wang, Guilin; Enderle, Markus; Awakowicz, Peter; Brucker, Sara Y.; Weiss, Martin (Frontiers in Medicine, 2025)
IntroductionHigh-grade squamous intraepithelial lesions (HSIL), such as cervical intraepithelial neoplasia grade 3 (CIN3), are precursors to invasive cancer. Although cancer develops in only 1–2 out of 10 patients with CIN3, all patients typically undergo invasive procedures. This overtreatment affects approximately 90% of CIN3 patients, especially young women, posing risks to fertility and pregnancy outcomes. Non-invasive physical plasma (NIPP) treatment via low thermal argon plasma devitalization (APD) technology offers a novel, outpatient alternative with potential tissue-preserving and antineoplastic properties.MethodsThis prospective, monocentric, randomized, controlled phase IIb trial (NCT04753073) evaluated the efficacy of APD in achieving histological remission of CIN3, compared to the natural course in an untreated control group. Forty premenopausal women aged 18 years or older with confirmed CIN3 were enrolled and randomized into two groups: 20 underwent a single APD treatment session followed by large loop excision of the transformation zone (LLETZ) 6–8 weeks later, and 20 served as untreated controls undergoing LLETZ only. Pain perception and patient satisfaction were assessed via visual analog scale and the Freiburg Index of Patient Satisfaction (FIPS), respectively. Statistical analyses included Fisher’s exact tests and odds ratio (OR) calculations and were conducted using SPSS.ResultsComplete histological remission of CIN3 was observed in 33.3% of APD-treated patients compared to 5.0% in the control group (p = 0.025, OR = 9.43). Partial remission occurred in 27.8% of APD patients and 15.0% of controls, while persistent CIN3 was more common in controls (80.0% vs. 38.9% in APD-treated patients). APD treatment also facilitated R0 resection during consecutive LLETZ in 94.4% of cases versus 65.0% in the control group (p = 0.082). No severe adverse events were reported, and patient satisfaction was comparable between groups.ConclusionAPD treatment demonstrates significant efficacy in inducing histological remission of CIN3, reducing lesion severity, and preserving tissue. This innovative approach offers a promising, minimally invasive alternative to conventional surgical methods, particularly for women of childbearing age. Given the current issue of overtreatment with invasive procedures, APD could significantly reduce unnecessary interventions. Larger, multicenter trials are warranted to confirm these findings and establish APD as a standard treatment for HSIL.Clinical trial registrationhttps://www.clinicaltrials.gov/study/NCT04753073, identifier NCT04753073.